Vita magistra historiae? Life experience and meanings of the past - Petri, Rolf (Historein, 2016)
The article tackles the question of how the historian’s personal experience interacts with professional choices. To assess in an experimental manner the methodological reach of autobiographical narration, the author considers his own case. In a first step he narrates how he was politicised in the 1970s and what history had to do with it. In a second step he reflects on his early professional activities and ponders how the turning point of 1989 interfered with his changing interests in the past. The final part is devoted to more general considerations regarding the influence of life experience on doing history. While the author’s experience confirms that biography influences professional choices, his theoretical and methodological argumentation rejects the idea that autobiographical writing should account for a new subjectivity paradigm in historiography.